Familial clustering and genetic heterogeneity in Meniere's disease. (9th April 2013) - Requena, T.; Espinosa‐Sanchez, J.M.; Cabrera, S.; Trinidad, G.; Soto‐Varela, A.; Santos‐Perez, S.; Teggi, R.; Perez, P.; Batuecas‐Caletrio, A.; Fraile, J.; Aran, I.; Martin, E.; et al.
<x xml:space="preserve">Abstract</x> The aims of this study were to estimate the prevalence of familial cases in patients with Meniere's disease (MD) and to identify clinical differences between sporadic and familial MD. We recruited 1375 patients with definite MD according to the American Academy of Otolaryngology‐Head and Neck Surgery criteria, obtaining the familial history of hearing loss or episodic vertigo by direct interview or a postal survey in 1245 cases in a multicenter study. Familial clustering was estimated by the recurrence risk ratio in siblings (λs) and offspring (λo) using intermediate and high prevalence values for MD in European population. A total of 431 patients (34%) reported a familial history of hearing loss or recurrent vertigo and 133 patients had a relative with possible MD. After clinical reevaluation, 93 relatives in 76 families were diagnosed of definite MD (8.4%), including three pairs of monozygotic twins. λs and λo were 16–48 and 4–12, respectively. We observed genetic heterogeneity, but most families had an autosomal dominant inheritance with anticipation. No clinical differences were found between sporadic and familial MD, except for an early onset in familial cases. We may conclude that MD has a strong familial aggregation and that sporadic and familial MDs are clinically identical.